Ministry of Trade and Industry Decree No. 24 of the year 2017 Amended By Decree No. 526/2018 = وزارة التجارة والصناعة قرار رقم 24 لسنة 2017 معدل بالقرار الوزراى رقم 526/2018 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic